The Implementation of Information Gap in Speaking - Irma Aulia Rahmah (Research in English and Education Journal, 2018)
This research investigates the implementation of information gap as a technique to improve the speaking skill for first year students of SMPN 2 Banda Aceh. The kind of experiment is quasi experimental design. This study involved two clasess as samples in this research, namely experimental group and control group. The experimental group was taugth by implementing information gap, while the control group was taught by implemeting conventional teaching. The students’ achievement was scored by using pre-test and post-test. To find out the result of this study, the writer used t-test score. The research finding shows that the mean score of post-test of the experimental group after implementing treatment is 95.02, higher than that of the control group, that is 70.6. In this reseearch, the writer took the the critical vaue of 2.704 for t at the level of significance 0.01. The researcher found that the pre-test t-value is lower than t-table (2.09 2.704). Afterward, the result of t-score of post-test is higher than pre-test (22.77 2.704). Therefore it can be concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. It indicated that there is a significant difference between the students who were taught speaking by using information gap and those who were not. In other words, information gap was an effective technique to improve students’ language skils especially in speaking skill.